The Effect of Tourism Attraction and Business Models on SMEs Income - Supriono, Supriono; Kurniawan, Andy; Agustin, Ornia (Journal of Industrial Engineering & Management Research, 2022)
This study aims to determine the effect of tourist attractions and business models on the income of SMEs in the Soerjo Ngawi Monument tourist area. The research method used in this study uses a quantitative approach by distributing questionnaires to respondents. The independent variables in this study are tourist attractions (X1) and business models (X2), while the dependent variable in this study is the income of SMEs (Y). The sample and population used in this study were 55 respondents. The results of this study show significant results that the effect of tourist attraction (X1) and business model (X2) on SME income (Y) is 35.8%.